Media Informasi Credit Sales Of Cooperative Electronic Goods PT. Nagasakti Paramashoes Industry - Bayu Pramono; Desi Astriyani; Helen Eka Nur Anggraini (UNIVERSITAS RAHARJA, 2021)
The information media has now developed, so that it has been widely used in various activities. In its use, information media has been used to assist the company's ongoing business systems in a company. A company that needs it is PT. NPI which operates in the manufacturing industry. The credit sales system related to electronic goods at the company is still not optimal and has started in today's companies. The currently ongoing installment input process for members is still using manual recording and still using Ms. Excel, so there are obstacles to the company and the inefficiency of the information that has been provided. Then the reporting process by employees is still not optimal. In this problem, therefore the researcher tries to apply the SWOT analysis method and the results of the completion of this research are in the form of credit sales information media related to electronic goods that can help employees deliver more maximum service, so that the information provided can be more effective and efficient.